PREDICTING DISAGGREGATED TOURIST ARRIVALS IN SIERRA LEONE USING ARIMA MODEL - JACKSON, Emerson Abraham; TAMUKE, Edmund (Theoretical and Practical Research in Economic Fields, 2019)
This study has uniquely made use of Box-Jenkins ARIMA models to address the core of the three objectives set out in view of the focus to add meaningful value to knowledge exploration. The outcome of the research has testified the achievements of this through successful nine months out-of-sample forecasts produced from the program codes, with indicating best model choices from the empirical estimation. In addition, the results also provide description of risks produced from the uncertainty Fan Chart, which clearly provide possible downside and upside risks to tourist visitations in the country. In the conclusion, it was suggested that downside risks to the low-level tourist arrival can be managed through collaboration between authorities concerned with the management of tourism in the country.